A follow up study of discharged COVID-19 patients admitted at tertiary care hospital of Ahmedabad city - Patel, Mansi; Khanpara, Hardika; Prajapati, Arpit; Thakar, Parth (Indian Journal of Community Health, 2022)
Introduction: Though there is limited information on late sequelae of COVID-19, reports of persistent symptoms in persons who recovered from COVID-19 illness have emerged. The most frequently reported symptoms include fatigue, shortness of breath, cough. Objectives: 1.To identify the persistence or development of various symptoms among discharged COVID-19 patients 2.To study the outcome of COVID-19 infection after one month of discharge 3.To assess the difference in the quality of life pre and post COVID-19 status of study participants by using EuroQol Visual Analogue scale. Material & Methods: A Longitudinal study was carried out among all discharged confirmed COVID-19 patients aged more than 18 years and above in 1st December 2020 to 31st December 2020. 50% of patients discharged in December 2020 were selected by simple random sampling method. Status of present symptoms at the time of discharge and after one month of discharge were taken through telephonic interview. Results: COVID-19patients had persistent symptoms like fatigue, cough, & anosmia respectively at the time of discharge. 7 (4.6%) patients found dead at the time follow up after one month. According to EQ-VAS, 79 (52.3%) COVID-19 patients perceived improved quality of life at the time of follow up one month after discharge as compare to the time of discharge. Conclusion: There is significant improvement in quality of life seen among the patients at the time of follow up than at the time of discharge. At the time of follow up, 4.6% deaths observed and some patients had persistent symptoms like fatigue, dyspnea.